Wind power prediction based on PSO-Kalman - Li, Daoqing; Yu, Xiaodong; Liu, Shulin; Dong, Xia; Zang, Hongzhi; Xu, Rui (Energy reports, 2022)
Because of its clean and green, wind power is broadly used all over the world. Wind power is random and unstable, so wind power integration will inevitably bring great impact to power system. Accurate wind power prediction can effectively alleviate the impact caused by wind power uncertainty. In order to increase the accuracy of wind power prediction, this article uses paper swarm optimization algorithm (PSO) to improve the traditional Kalman filter, and PSO-Kalman wind power point prediction model is established. The proposed model solves the problem of low prediction accuracy of traditional Kalman filter caused by observation noise and process noise. Finally, based on point prediction error, non-parametric kernel density estimation is used for interval prediction. By experimental simulation, by comparing the error evaluation indexes of point prediction and interval prediction, it can be found that the point prediction error of PSO-Kalman is the smallest, indicating that PSO can effectively improve the prediction accuracy of Kalman. On this basis, the interval prediction performance is also better than before. Moreover, the model proposed in this article converges fast and has better general applicability.